The Effect of Self-Regulated Learning Strategy on Student Learning Outcomes in Acid-Base Titration Material - Salsabila, Marisa; Muchlis, Muchlis (Lectura : Jurnal Pendidikan, 2024)
This research is based on the fact that students' learning outcomes in acid-base titration material in the low scores. The aim of this research is to investigate the effect of self-regulated learning strategies in acid-base titration material on student learning outcomes. This research was quantitative research with a pre-experimental design with a one group pretest posttest design. This research began with a pretest, then at meeting 1, posttest 1 was given. After that, the implementation of Self-Regulated Learning (SRL) continued with posttest 2. The subjects used were 34 students at one of the State High Schools in Gresik. The instruments used were pretest and posttest sheets. Data analysis used was hypothesis testing and N-gain testing. Hypothesis testing showed that there was a significant difference between pretest and posttest 1 as well as between posttest 1 and posttest 2. Meanwhile the N-gain test shows that there was an improvement in learning outcomes from pretest and posttest 1 as well as from posttest 1 and posttest 2. The percentage of students who gain N-gain with medium criteria at meetings 1 and 2 was respectively 61.76% and 23.52% and for high criteria respectively 38.23% and 76.47%. The results of the hypothesis test and N-gain test showed that there was a positive influence on student learning outcomes in the acid-base titration material. Therefore, it can be concluded that SRL strategy-oriented learning influences learning outcomes and can improve student learning outcomes in acid-base titration material.